Kontribusi Kompetensi Pedagogik dan Profesional Guru terhadap Hasil Belajar Siswa pada Mata Pelajaran Instalasi Penerangan Listrik - Risti, Aisya Shofanadhiya; Aswardi, Aswardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This research was conducted to determine how much pedagogic competence and professional competence of teachers contribute to student learning outcomes in the subject of electrical lighting installation at SMK Negeri 5 Padang. This research is a quantitative study using the correlation analysis method. The sample in this research amounted to 36 students in class XI TITL SMK Negeri 5 Padang in the 2022/2023 school year. Data collection was carried out using questionnaires and documentation, with a questionnaire instrument scored using a Likert scale. Before the questionnaire was used for testing and distributed to respondents, it was first validated by an experienced validation lecturer in the Electrical Engineering department. For hypothesis testing, the correlation test was used and for the significance of the correlation, the t-test was used to partially test the effect between the independent and dependent variables. The results of this study indicate that (1) There is a positive and significant influence between the pedagogical competence of teachers on learning outcomes. (2) There is a positive and significant influence between the professional competence of teachers on learning outcomes (3) There is a positive and significant influence between pedagogic and professional competence of teachers together on student learning outcomes. It can be concluded that teachers' pedagogic and professional competencies contribute to students' practical learning outcomes. Therefore, every teacher needs to improve these competencies to achieve satisfactory student learning outcomes.